Study on Hearing Impairment in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Hearing impairment is one of the leading causes of disability in Bangladesh. Since half the cases can be prevented through public awareness, early detection and timely management, planning of public health interventions become necessary. To achieve this, a nationwide level of evidence is required. This survey was conducted with the aim of determining the prevalence of hearing impairment in Bangladesh.Materials and methods : The study was a cross-sectional one, conducted between January to May 2013, where a multistage, geographically clustered sampling approach was used. A total of 52 primary sampling units were selected, and from each unit households were selected at random followed by random selection of an individual from each household. In total, 5,220 people were targeted out of which data collection could be completed from 4260 individuals. (82%). Following clinical assessment of study subjects, hearing status was assessed by pure tone audiometry and otoacoustic emission test.Results : The mean age was 32 years among which 58% were females. Among men, there were 29% students, 28% agriculture workers and 14% business men. A major portion of females (63%) were home makers. On clinical examination, 11.5% respondents had impacted ear wax, 6.2% had chronic middle ear infections with eardrum perforation, and 5.3% had otitis media with effusion.On hearing assessment, 34.6% respondents had some form of hearing loss (>25dB in better ear). Conductive hearing loss was found in 12.0%, sensorineural in 4.5% and mixed in 3.8%, where the latter two increased in prevalence with age. Out of the total respondents, 9.6% had disabling hearing loss according to WHO criteria, with a higher prevalence in adults > 60 years(37%). Logistic regression analysis showed age, socioeconomic status, presence of ear wax, chronic suppurative otitis media, otitis media with effusion and otitis externa were significant predictors of disabling hearing loss.Conclusion : The major causes of conductive hearing loss are chronic suppurative otitis media and otitis media with effusion.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 72-76